Pendidikan dan Pendapatan Terhadap Mobilitas Sosial Wanita di Gampong Laksana Banda Aceh - Diani Khairunnisa; Alamsyah Taher (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2017)
ABSTRACT Keywords: education, income, social mobilityThis study, entitled Education and Income on Social Mobility Women in Gampong Laksana Banda Aceh raised the issue of (1) the role of education and income against the social mobility of women in the Village Laksana Banda Aceh (2) what was in the charge of education and income that contributes to social mobility of women in Like a Gampong Banda Aceh. This study aimed to (1) the role of education and income against the social mobility of women in the Village Laksana Banda Aceh and (2) the contents of the charge of education and income that contributes to social mobility Gampong Like a woman in Banda Aceh. This research subject female workers in Gampong Laksana totaling 581 people. Decision informants selected by purposive sampling a total of 11 people. The method used qualitative descriptive method. The data collection is done by observation and interview techniques and data processing using qualitative analysis, the data that has been collected in the reduction, followed by the presentation of the data is verified and do conclusion. The results showed the role of education was instrumental in increasing revenue because educated women have a greater opportunity to move from one job to another. Based on the results of the study conclude that 1) women in Gampong Like an educated employment and incomes were more feasible, 2) the education there is guidance on how a woman to be able to get a better income with the opportunity to obtain information about what work should be done that encourages women Gampong Laksana move from one job to another. Suggested research on social mobility can be continued by other researchers so that it can be revealed things that have not been revealed.